Digitizing Da'wa Movement of Pesantren Baitul Hidayah Through Productive Waqf (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
The trend of millennial Muslims is currently learning religion through online media. The challenge is not all religious information in online media follows the wasathiyah source of Islamic teachings. Thus, Islamic boarding schools as religious institutions must seek to provide religious information through da'wah's digitization. To meet the need for digitizing da'wah, Islamic boarding schools can take advantage of productive waqfs, such as the Baitul Hidayah Islamic Boarding School. This study uses a qualitative descriptive approach with data sources obtained through interviews, documentation, and observation. The purpose of the study was to obtain an overview of the use of Productive Waqf as the capital of Baitul Hidayah Islamic Boarding School in the digital da'wah movement. The results showed that the development of the digital da'wah movement through the use of productive waqf at the Baitul Hidayah Islamic Boarding School was carried out in several ways, including strengthening Islamic boarding school management resources by forming an exceptional team with multimedia capabilities from content planning, editing, and publication on social media. In addition, through productive waqf, Baitul Hidayah Islamic Boarding School also facilitates the provision of adequate digital infrastructure and a particular multimedia room for producing digital da'wah content. The development of a digital da'wah movement through productive waqf at the Baitul Hidayah Islamic Boarding School is also carried out by selecting a dai capable of religious, scientific capacity to present quality and interesting da'wah content, especially for Muslim millennials.